1993
DOI: 10.1017/s0021932000020733
|View full text |Cite
|
Sign up to set email alerts
|

Teenage sexual activity in Zambia: the need for a sex education policy

Abstract: SummaryData from a study of teenage sexual activity among secondary school girls show the need for a sex education policy as a first step in controlling teenage fertility in Zambia. A large proportion of teenage females enter into close relationships with males at young ages and a high proportion of young females have engaged in sexual intercourse. Most of these sexually active females do not use family planning methods even though a large proportion of them have heard of modern methods. The teenagers receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…On the contrary, the Catholic religion was found to be encouraging education of adolescents about abortion in the Philippines. 12 Regarding information from the household, it was found that teenagers received very little sex education from their parents in Zambia, 13 which could be due to the fact that talking about sex is often still regarded as taboo in many African societies, including the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the Catholic religion was found to be encouraging education of adolescents about abortion in the Philippines. 12 Regarding information from the household, it was found that teenagers received very little sex education from their parents in Zambia, 13 which could be due to the fact that talking about sex is often still regarded as taboo in many African societies, including the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was designed after a needs assessment was conducted that included focus group interviews with adolescents [12] and a review of literature on Zambian adolescents [e.g. [13][14][15][16].…”
Section: The Zambia Peer Sexual Health Interventionmentioning
confidence: 99%
“…To ensure that the intervention would be in sync with the social context in which Zambian adolescents develop their attitudes toward sexual behavior, the design of the SFH intervention was informed by focus groups with adolescents (Mwaba, 1999) and findings from other studies in Zambia (Campbell & Kelly, 1995;Pillai & Kelley, 1993;Pillai & Yates, 1993;van den Borne, Tweedie, & Morgan, 1996). Based on this information, a peer sexual health intervention was designed that focused on several important areas/issues simultaneously.…”
Section: The Sfh Peer Sexual Health Interventionmentioning
confidence: 99%